Synthesis and Antibacterial Activity of Antibiotic-Functionalized Graphite Nanofibers. (25th February 2015) - Rotella, Madeline; Briegel, Alicia; Hull, John; Lagalante, Anthony; Giuliano, Robert
Abstract : Surface functionalization of nanomaterials is an area of current investigation that supports the development of new biomaterials for applications in biology and medicine. Herein we describe the synthesis, characterization, and antibacterial properties of the first examples of antibiotic-labeled graphitic carbon nanofibers (GCNFs) covalently functionalized with aminoglycoside and quinolone antibiotics. Ruthenium tetroxide oxidation of herringbone GCNFs gave higher amounts of surface carboxyl groups than previous methods. These carboxyl groups served as sites of attachment for antibiotics by acyl substitution. Bioassay of these novel, functionalized GCNFs using serial dilution and optical density methods demonstrated that antibiotic-labeled GCNFs possess significant antibacterial activity against Pseudomonas aeruginosa . The activity we observe for aminoglycoside-functionalized GCNFs suggests a membranolytic mechanism of action.